Overexpression of the rat inducible 70-kD heat stress protein in a transgenic mouse increases the resistance of the heart to ischemic injury. - Marber, M S (1995)
Myocardial protection and changes in gene expression follow whole body heat stress. Circumstantial evidence suggests that an inducible 70-kD heat shock protein (hsp70i), increased markedly by whole body heat stress, contributes to the protection. Transgenic mouse lines were constructed with a cytomegalovirus enhancer and beta-actin promoter driving rat hsp70i expression in heterozygote animals. Unstressed, transgene positive mice expressed higher levels of myocardial hsp70i than transgene negative mice after whole body heat stress. This high level of expression occurred without apparent detrimental effect. The hearts harvested from transgene positive mice and transgene negative littermates were Langendorff perfused and subjected to 20 min of warm (37 degrees C) zero-flow ischemia and up to 120 min of reflow while contractile recovery and creatine kinase efflux were measured. Myocardial infarction was demarcated by triphenyltetrazolium. In transgene positive compared with transgene negative hearts, the zone of infarction was reduced by 40%, contractile function at 30 min of reflow was doubled, and efflux of creatine kinase was reduced by approximately 50%. Our findings suggest for the first time that increased myocardial hsp70i expression results in protection of the heart against ischemic injury and that the antiischemic properties of hsp70i have possible therapeutic relevance.